2012
DOI: 10.1038/nm.2695
|View full text |Cite
|
Sign up to set email alerts
|

Functional engraftment of colon epithelium expanded in vitro from a single adult Lgr5+ stem cell

Abstract: Adult stem-cell therapy holds promise for the treatment of gastrointestinal diseases. Here we describe methods for long-term expansion of colonic stem cells positive for leucine-rich repeat containing G protein-coupled receptor 5 (Lgr5(+) cells) in culture. To test the transplantability of these cells, we reintroduced cultured GFP(+) colon organoids into superficially damaged mouse colon. The transplanted donor cells readily integrated into the mouse colon, covering the area that lacked epithelium as a result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
606
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 712 publications
(636 citation statements)
references
References 33 publications
10
606
0
3
Order By: Relevance
“…DSS-induced acute colitis is a widely employed model to study colitis, which is thought to be provoked by inflammation 13,38,39 . However, recent studies suggest that damage of colonic stem cells could be a major cause [13][14][15] . In addition, disruption of epithelial cell contacts could be important in the pathological process as the loss of tight junctions of colonic epithelial cells was observed in DSS-induced colitis [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DSS-induced acute colitis is a widely employed model to study colitis, which is thought to be provoked by inflammation 13,38,39 . However, recent studies suggest that damage of colonic stem cells could be a major cause [13][14][15] . In addition, disruption of epithelial cell contacts could be important in the pathological process as the loss of tight junctions of colonic epithelial cells was observed in DSS-induced colitis [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…As colonic epithelium injuries are critical for colitis initiation [13][14][15] , we then accessed whether Myh9 monoallelic loss could alleviate DSS-induced acute colitis. The disease activity index (DAI) has been commonly used to evaluate the grade and extent of acute colitis 18 .…”
Section: Myh9 Monoallelic Deletion Ameliorates Dss-induced Colitismentioning
confidence: 99%
See 1 more Smart Citation
“…The Clevers' Laboratory paved the way by capitalising on their seminal work on Wnt signalling, intestinal stem cells and cancer [8][9][10], and developed the mouse small intestinal organoid culture system [11,12]. This 'mini-gut' culture system formed the basis for the development of human organoid cultures from the intestinal epithelium [13,14,1] and from (inducible) pluripotent stem cells [15], both of which hold the potential for therapeutic transplantation [16,17]. For the study of native intact human colonic crypts, we adopted a similar approach whereby crypts are embedded in a basement membrane-derived matrix, Matrigel [18], instead of collagen I [7], and serum-free culture medium is supplemented with the intestinotrophic factors IGF-1 (activator of RAS signalling pathway) and R-spondin (activator of Wnt signals) in combination with inhibitors of BMP (Noggin or Gremlin proteins) and TGF (SB431542 or A83-01 small molecules) signalling pathways [18].…”
Section: Human Colonic Crypt Culturementioning
confidence: 99%
“…Additionally, recent work by the Watanabe laboratory (2012) [47] showed that organoids retain the functionality of the intestine when transplanted back into test animals. This was demonstrated by elegant transplantation experiments showing that GFP-labeled organoids can replace damaged colonic tissue when transplanted into colons of mice that had been treated with the colitis inducing chemical dextran sodium sulfate (DSS) [47]. Together these experiments demonstrate that stem cells cultured within organoids retain the capacity for stem cell self-renewal and differentiation.…”
Section: Organoids: 3-dimensional Mini-guts In a Dishmentioning
confidence: 99%